Tarantula cubensis extract and low-level laser therapy: a histopathological, radiological and serological analysis of bone repair on an experimental bone - Semih ALTAN; Hakan SAĞSÖZ; Berna ERSÖZ KANAY; Feray ALTAN; Emel ALAN; Remzi ÇEVİK (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2023)
In this study, it was aimed to investigate the effects of tarantula cubensis extract (TCE) and low-level laser therapy (LLLT) on cancellous and cortical bone repair. A circular unicortical bone defect was created on both the cancellous and cortical regions of the tibia of each subject. The subjects, totaling 54 mature New Zealand rabbits, were randomly allocated into three groups (n:18 each): control, LLLT (Galium-aliminum-arsenide laser at a wavelength of 780 nm and 4 J/cm2, 5 min/day) and TCE (1 μg/kg) groups. Relative optic density (ROD) level was higher in the TCE group than the control group on day 28 as radiological (P<0.05). In both cancellous and cortical bone, inflammatory cell densities were less on the 14 and 21st day in the TCE and LLLT groups, bone tissue formation and qualities were higher 7 and 14th days in TCE and LLLT and collagen maturation were higher 28th day in the TCE group as histopathological (P<0.05). In this study, TCE accelerates bone repair as much as LLLT and more than the control group. In conclusion, that TCE is an effective, easier to apply and more economical supportive treatment in bone defects like LLLT.